2001
DOI: 10.1017/s0012162201
|View full text |Cite
|
Sign up to set email alerts
|

Adults with cerebral palsy: a survey describing problems, needs, and resources, with special emphasis on locomotion

Abstract: The purpose of this study was to describe problems and resources of adults with cerebral palsy (CP) with special emphasis on locomotion. A questionnaire concerning demographic facts, locomotion, musculoskeletal problems, and present physical activity was mailed to 363 adults with CP. Two hundred and twenty-one adults, (125 male and 96 female; mean age 36 years, range 20 to 58 years) answered the questionnaire. Seventy-seven per cent reported problems with spasticity. Eighty-four per cent lived in their own apa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
236
7
16

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(269 citation statements)
references
References 8 publications
10
236
7
16
Order By: Relevance
“…While the solutions discovered by children with cerebral palsy may work in the short term, there may be untoward long and short-term consequences. For example, a child who essentially uses a running-like gait pattern is susceptible to early fatigue, and accelerated wear and tear on the joints 97,98 . In any case, the solutions discovered lead to easy fatigue, itself a constraint on locomotor ability.…”
Section: Implications For Rehabilitationmentioning
confidence: 99%
“…While the solutions discovered by children with cerebral palsy may work in the short term, there may be untoward long and short-term consequences. For example, a child who essentially uses a running-like gait pattern is susceptible to early fatigue, and accelerated wear and tear on the joints 97,98 . In any case, the solutions discovered lead to easy fatigue, itself a constraint on locomotor ability.…”
Section: Implications For Rehabilitationmentioning
confidence: 99%
“…A few small studies have been published on education and employment among young adults with CP based on somewhat different methods (Kokkonen et al 1991, O'Grady et al 1995, Murphy et al 2000, Andersson and Mattsson 2001. Murphy et al (2000) included 101 specially selected individuals with CP in the US: 53% were competitively employed.…”
mentioning
confidence: 99%
“…Kokkonen et al (1991) studied 52 individuals with CP aged 19 to 26 years from the same hospital area in Finland: 38% were working. A study in Sweden (Andersson and Mattsson 2001) included 221 individuals with CP from the same county without documented learning disability who responded to a mailed questionnaire: 24% were working full time.…”
mentioning
confidence: 99%
“…Furthermore, Fowler and colleagues (2007) reported greater weakness in the distal musculature in comparison with the proximal musculature in people with CP, difference that may be responsible for the difficulties in locomotion that CP patients suffer. As a result of this difference in muscular strength, a study reported that 51% of the subjects with CP analysed in that work could not walk or needed orthopaedic help to carry out the task (Andersson & Mattsson, 2001).…”
Section: Discussionmentioning
confidence: 99%